Pengembangan Media Pembelajaran Berbasis Google Sites Berbentuk E-Book Materi Kegiatan Ekonomi Mata Pelajaran Ilmu Pengetahuan Sosial Kelas IV Sekolah Dasar - Yuanta, Friendha; Putri, Syafana Azelita; Amelia, Hikmah Putri; Qur’aini, Qori Ulil; Rasmi, Sita Satya; Santoso, Vica Alverina Auria (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the feasibility and effectiveness of Google Sites-Based Learning Media in the form of E-Books for the subject